Kuantitas dan Kualitas Larva Ikan Nila (Oreochromis niloticus) Hasil Pemijahan Induk dengan Sex Ratio Berbeda - Sinaga, Ade Angelia Atmanegara; Julyantoro, Pande Gde Sasmita; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 3 No 2 (2020), 2020)
The prospect of developing freshwater fish farming development in Indonesia has been promising. One of the freshwater fish commodities that has a high economic value and market demand is tilapia ( Oreochromis niloticus ). This research aims to determine the optimal sex ratio for tilapia broodstock to produce the best quantity and quality of tilapia larvae. The research was conducted in December 2019 to February 2020 at Unit Pelaksana Teknis (UPT) Pasar Benih Ikan dan Balai Benih Ikan Denpasar. The method use is an experimental with complete random design with 3 treatments and 3 replicates. The sex ratio for this research was a ratio between males and females of 1:2, 1:3, 1:4. Observed parameters were fish larvae quantity, absolute weight and length tilapian larvae, survival rate tilapia larvae and water quality. The results of this research showed that sex ratio of tilapia has a significant effect ( P < 0,05) on the quantity of tilapia larvae, with the highest quantity was obtained from the treatment B (sex ratio of 1:3) about 1305±393 individu, but the quality of the tilapia larvae e.g. absolute weight, length and survival rate were not significantly influenced by sex ratio of tilapia broodstock ( P > 0,05). Water quality parameter including temperature, dissolved oxygen (DO) and potential of hydrogen (pH) were still at a range that supports tilapia life during the research period. Keywords: Tilapia; Larvae; Mating; Sex Ratio